Band Aid revisited: humanitarianism, consumption and philanthropy in the 1980s. Issue 2 (3rd April 2017) - Jones, Andrew
Abstract: This article revisits the iconic Band Aid phenomenon of 1984–1985. The analysis sets out to historicise and contexualise Band Aid within the 1980s as a decade, and contemporary British history more broadly. The central argument is that Band Aid was not as epochal as often assumed, instead fitting into a longer history of humanitarianism and charitable fundraising in Britain. However, Band Aid still remains an important signpost for how British society was reshaped during the 1980s by far-reaching changes in capitalism, popular culture, governance and technology. Band Aid both reflected and reinforced an ongoing shift in the legitimacy of charity and welfare, away from state-led welfare solutions towards more individualised and market-driven forms of action articulated through the realms of consumption and mass culture. This form of marketised philanthropy was highly effective at stimulating public donations, but it did so by shunning overt engagement with the underlying causes of global hunger and poverty.